Last-Minute Bidding and the Rules for Ending Second-Price Auctions: Evidence from eBay and Amazon Auctions on the Internet - Roth, Alvin E; Ockenfels, Axel (American Economic Review, 2002)
Last-Minute Bidding and the Rules for Ending Second-Price Auctions: Evidence from eBay and Amazon Auctions on the Internet by Alvin E. Roth and Axel Ockenfels. Published in volume 92, issue 4, pages 1093-1103 of American Economic Review, September 2002